Analisis Manfaat Penyertaan Modal Negara Pada Program Pembangunan Infrastruktur Listrik Desa Provinsi Bali - Heru Akhmadi; Putu Nanda Priastawa (Bina Ekonomi, 2021)
Infrastructure in Indonesia needs to be developed every year following the economic growth of Indonesia and the world. Regarding the availability of electricity resources, there are still many households in rural Bali that do not have electricity facilities so that rural communities cannot be fully productive economically. This study aims to measure the effectiveness of government investment through State-owned Equity Participation to the State Electricity Company (PT. PLN) in the Java-Bali electricity infrastructure development program, especially in the village electricity program in Bali Province. This study uses a qualitative method using Atlas.ti software to analyze the results of interviews by providing codes in the form of a collection of words that are most relevant and needed in research. This study also calculates the benefits of government investment through a cost and benefit analysis approach. The results show that the Java-Bali electricity infrastructure development program, especially the village electricity program in Bali Province, has effectively increased the electrification ratio by 100%. Other results show other benefits of village electricity projects such as increasing productivity, cost and energy efficiency, improving living standards, adding insight and information, and also facilitating small and medium enterprises in the villages of Bali Province.